Analysing the Meaning of Audience for Cross-gender Artists in the Documentary Lelaki Ayu Primadona Java: Lengger Lanang - Safira Nur Ujiningtyas (Fakultas Komunikasi, Sastra, dan Bahasa, 2024)
Lengger Lanang is a traditional Javanese dance performed by a group of men that dress like women. This tradition might clash with a conservative Indonesian culture that considers cross-dressing men as deviant. This research aims to analyze how a group of people perceive a documentary film titled Lelaki Ayu Primadona Jawa: Lengger Lanang about a group of Lengger Lanang dancers. Using Stuart Hall’s encoding-decoding theory, this research involved seven informants who were divided into three groups of reader positions: dominant, negotiation and opposition. This research used a descriptive qualitative research design which focuses on the audience's reading position by analyzing the audience's understanding of cross-gender artists through documentary film scenes. Data was obtained from in-depth interviews with the informants. The research results showed that four informants who were in dominant positions and three informants who were in negotiating positions, and there were no audience members who were in opposition positions. The audience's reading position is influenced by the background of the audience watching the documentary. The audience interprets this documentary as an understanding of artists across gender but also discusses the preservation of the culture, history and values ​​of the Lengger Lanang dancers.